Effect of Ni-coated carbon nanotubes on interfacial reaction and shear strength of Sn-Ag-Cu solder joints - Nai, S. M. L. (2013)
In this study, varying weight percentages of Ni-coated carbon nanotubes (Ni-CNTs) were incorporated into Sn-Ag-Cu (SAC) solder matrix, to form composite solder. Up to 0.05% of Ni-CNTs were successfully incorporated. The interfacial microstructure and shear strength of solders on Ni/Au-finished Cu substrates were investigated after aging at 150°C for up to 42 days. Results revealed that, after soldering and aging for various lengths of time, the interfacial intermetallic compound (IMC) thickness of the unreinforced solder joint was observed to grow more significantly than that of the composite solder joints. Furthermore, the composite solder joints also showed lower diffusion coefficients (2.5 × 10−15 cm2/s to 3.2 × 10−15 cm2/s) compared with that of the SAC solder joints (4.9 × 10−15 cm2/s). Shear test results revealed that as-soldered and aged composite solder joints had better ultimate shear strength than their monolithic counterparts and the shear strength of all aged solder joints decreased with increasing aging time.